2016
DOI: 10.1159/000443068
|View full text |Cite
|
Sign up to set email alerts
|

Periostin Contributes to Cisplatin Resistance in Human Non-Small Cell Lung Cancer A549 Cells via Activation of Stat3 and Akt and Upregulation of Survivin

Abstract: Background/Aims: Periostin is upregulated in non-small cell lung cancer (NSCLC). This study was done to explore the function of periostin in the development of cisplatin (CDDP) resistance in NSCLC. Methods: The effects of overexpression or knockdown of periostin on CDDP sensitivity was examined in A549 cells. The involvement of signal transducer and activator of transcription 3 (Stat3) and Akt signaling in the action of periostin was checked. The in vivo effect of periostin silencing on CDDP susceptibility was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 30 publications
2
37
1
1
Order By: Relevance
“…McCarroll has reported that loss of PTEN/AKT activity can promote tumorigenesis in NSCLC, which explains the changes in proliferation and cell cycle between the treated and control cells [41]. Additionally, as a downstream molecule of many regulatory factors, such as miRNA-10a, TOPK/PBK, PUMA and others, PTEN/AKT has been shown to influence the drug resistance and prognosis of NSCLC [37, 42-44]. Furthermore, we reduced the expression of PTEN in FAL1 knockdown cells and found that the effect of FAL1 siRNA interference was partially rescued, which demonstrated our assumption of the presence of a FAL1-PTEN/AKT-EMT regulation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…McCarroll has reported that loss of PTEN/AKT activity can promote tumorigenesis in NSCLC, which explains the changes in proliferation and cell cycle between the treated and control cells [41]. Additionally, as a downstream molecule of many regulatory factors, such as miRNA-10a, TOPK/PBK, PUMA and others, PTEN/AKT has been shown to influence the drug resistance and prognosis of NSCLC [37, 42-44]. Furthermore, we reduced the expression of PTEN in FAL1 knockdown cells and found that the effect of FAL1 siRNA interference was partially rescued, which demonstrated our assumption of the presence of a FAL1-PTEN/AKT-EMT regulation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis was also confirmed by luciferase reporter assays, Western blotting and RT-PCR. STAT3 has been extensively demonstrated to play a critical role in the tumorigenesis of various human malignancies [25]. For example, increased activation of STAT3 is a characteristic of various tumors and tumor cell lines [26, 27].…”
Section: Discussionmentioning
confidence: 99%
“…As a cytoplasmic transcription factor that modulates the transcription of a variety of genes and regulates several biological functions including proliferation, differentiation, angiogenesis, progression and metastasis, constitutive activation of Stat3 was involved in oncogenic transformation and progression in several cancer types [52-54]. We observed that inactivation of Stat3 phosphorylation (Tyr705) was occurred in the anti-lung cancer effect of solamargines.…”
Section: Discussionmentioning
confidence: 99%